204 EPIDEMIOLOGY AND CLINICAL MANIFESTATIONS OF HUMAN METAPNEUMOVIRUS INFECTIONS AMONG CHILDREN IN MOBILE, ALABAMA. (1st January 2006) - Carter, M.; Estrada, B.; Barik, S.; Vidal, R.; Ramsey, K. M.
Abstract : Background: Human metapneumovirus (hMPV) is a recently described respiratory pathogen of children. However, there have been no data available regarding the epidemiology and clinical manifestations of hMPV infection in our geographical region. Methods: A prospective cross-sectional evaluation of children 0-18 years old presenting to our university hospital and clinics with symptoms of respiratory infection was conducted during the months of November-April 2004. Following informed consent, parents were interviewed and respiratory specimens collected by nasopharyngeal or endotracheal tube aspiration. The samples were screened for the presence of hMPV by RT-PCR. When possible, respiratory samples were also analyzed for the presence of respiratory syncytial virus (RSV) and influenza virus by either rapid antigen detection or culture. Results: Seventy-three patients, ages 7 days to 12 years, were enrolled. At the time of enrolment, 26% of study subjects were outpatients and 74% were hospitalized due to dehydration and complications of acute respiratory illness. hMPV was isolated from 15% (11/73) of patients. Additionally, 17% (9/54) patients were positive for RSV and 19% (8/42) patients were positive for influenza. All patients in which hMPV was detected were hospitalized at the time of enrolment. Seventy-two percent of patients from whom hMPV was isolated were younger than 3 years. Underlying chronic medical conditions were identified among 63% of patients with hMPV infection and included prematurity, congenital heart disease, and neuromuscular disease. Clinical manifestations among patients with hMPV infection were fever (54%), cyanosis (45%), subcostal retractions (36%), decreased oral intake (36%), wheezing (10%), rhinorrhea (10%), and cough (10%). Abnormal radiographic findings were present in 100% of subjects with hMPV including hyperinflation (100%), perihilar infiltrates (72%), consolidation (9%), atelectasis (9%), and pneumothorax (9%). Conclusion: hMPV infection is a frequent cause of respiratory infections in our pediatric population. Abnormal radiographic examinations are common among hospitalized patients with hMPV in our institution. Underlying medical conditions may increase the risk of hospitalization among children infected with hMPV.